Estimation and Analysis of Wind Electricity Production Cost in Morocco - Tizgui, Ijjou; El Guezar, Fatima; Bouzahir, Hassane; Vargas, Alessandro N. (International Journal of Energy Economics and Policy, 2018)
The goal of this investigation is to evaluate, analyze and compare the cost of energy produced at nine wind farms in Morocco, namely Tarfaya, Fem El Oued, Essaouira, Tangier I, Haouma, Koudia al Baïda, Laayoune, Tetouan I and Tetouan II. We report the economic factors that influence the wind energy cost. Then, we give an easy and precise economic methodology to estimate it. The conducted analysis reveals that the minimum cost is attained at Koudia al Baïda park which is equal to 0.0164 €/kWh. The good result is obtained also at Essaouira, Tetouan I and Fem El oued with a cost less than 0.03 €/kWh. The parks where the energy cost is between 0.03 €/kWh and 0.04‎ €/kWh are Haouma, Tarfaya, Tetouan II and Tangier I. The park that generates energy with more than 0.04‎ €/kWh is Laayoune. The sensitivity analysis reveals that for the studied wind farms, the variables which have a greatest effect on the estimated wind energy cost are the interest rate, the produced energy and the project lifetime. The estimated energy cost is not very sensitive to the variation on operation and maintenance costs. The obtained results show also that for all the studied wind farms, the obtained costs of producing one kWh of energy are less than the purchase tariff of electricity in Morocco and compare favorably with solar energy production cost in Morocco. Thus, wind energy is economically beneficial in Morocco, which is due to the important wind resources and the available concessional finance. Keywords: Investment cost; Operation and maintenance cost; Annualized cost; Interest rate; Capital recovery factor; Levelized cost of energy. JEL Classifications: E4; Q4